A Review of Next-Generation Drug Delivery Systems And Technologies (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2023)
Recent drug delivery systems (DDS) are formulated using advanced technology to accelerate systemic drug delivery to the specific target site, maximizing therapeutic efficacy and minimizing off-target accumulation in the body [2]. As a result, they play an important role in disease management and treatment. This is especially true for most life-threatening diseases requiring therapeutic agents with numerous side effects, thus requiring accurate tissue targeting to minimize systemic exposure.Delivery strategies have greatly helped convert promising therapeutics into successful therapies. As the therapeutic landscape evolved, delivery strategies and technologies quickly adapted to changing drug delivery needs. A few decades ago, small-molecule drugs were the primary class of therapeutic [13].Drug delivery technologies have enabled the development of many pharmaceutical products that improve patient health by enhancing the delivery of a therapeutic to its target site, minimizing off-target accumulation, facilitating patient compliance, and enabling entirely new medical treatments [17].The components of the drug account for its physicochemical properties and are responsible for the changes it influences in the body. It, improves the drug solubility, target site accumulation, efficacy, pharmacological activity, pharmacokinetic properties, patient acceptance, and compliance, and reduces drug toxicity [2].Innovation in delivery technologies and strategies has been catalyzed by the identification of unique delivery challenges associated with each class of therapeutics. As the therapeutic landscape evolved, delivery strategies and technologies quickly adapted to reflect changing drug delivery needs.